The Influence Of Work Culture And Compensation On Intention To Stay With Knowledge Sharing As A Mediating Variable On Employees Of PT. Bank Pembangunan West Kalimantan Region Branch Sanggau - Monika, Utin Vera; Daud, Ilzar; Sulistiowati, Sulistiowati; Rosnani, Titik (Jurnal Ekonomi, 2024)
This study aims to test and analyze the influence of work culture and compensation on the intention to stay with various knowledge as a mediating variable on employees of PT Bank Kalbar, Sanggau Regency. The research method used is a type of causal research. The population of all employees of PT Bank Pembangunan Daerah Sanggau Regency, totaling 56 permanent employees and working ≥ 5 years. Data analysis using SPSS version 25.00 and WarpPLS. The results of the study revealed: employee work culture, compensation, influence the intention to stay of employees of PT Bank Kalbar, Sanggau Regency. Employee work culture, compensation, influence the knowledge sharing of employees of PT Bank Kalbar, Sanggau Regency. Employee knowledge sharing influences the intention to stay of employees of PT Bank Kalbar, Sanggau Regency. Employee work culture influences the intention to stay through knowledge sharing of employees of PT Bank Kalbar, Sanggau Regency. Employee compensation influences the intention to stay through knowledge sharing of employees of PT Bank Kalbar, Sanggau Regency.